2017
DOI: 10.1101/161497
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Acquisition of Resistance to Carbapenem and Macrolide-mediated Quorum Sensing Inhibition byPseudomonas aeruginosavia a Novel Integrative and Conjugative Element ICETn43716385

Abstract: Pseudomonas aeruginosa can cause persistant and life-threatening infections in immunocompromised patients. Carbapenems are the first-line agents to treat P. aeruginosa infections; therefore, the emergence of carbapenem-resistant P. aeruginosa strains has greatly challenged effective antibiotic therapy. In this study, we characterised the full-length genomes of two carbapenem resistant P. aeruginosa clinical isolates that produce the carbapebemase New Delhi metallo-β-lactamase-1 (NDM-1). We found that the blaND… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…A study by Lee et al [15] demonstrated that antibiotic resistance is formed quite rapidly in case of infection caused by gram-negative microorganisms. For instance, Stenotrophomonas maltophilia, Acinetobacter baumannii, Pseudomonas aeruginosa and Enterobacteriaceae strains that appear in many studies are nosocomial infection strains (pneumonia, catheter sepsis); they enter the patient's body before treatment with carbopenem, resulting in the production of βlactamases [29][30][31].…”
Section: Meropenemmentioning
confidence: 99%
“…A study by Lee et al [15] demonstrated that antibiotic resistance is formed quite rapidly in case of infection caused by gram-negative microorganisms. For instance, Stenotrophomonas maltophilia, Acinetobacter baumannii, Pseudomonas aeruginosa and Enterobacteriaceae strains that appear in many studies are nosocomial infection strains (pneumonia, catheter sepsis); they enter the patient's body before treatment with carbopenem, resulting in the production of βlactamases [29][30][31].…”
Section: Meropenemmentioning
confidence: 99%